Determination of Nifedipine in Human Plasma by Tandem Mass Spectrometry - BAVISKAR, DHEERAJ; SHARMA, RAJESH; JAIN, DINESH (Asian Journal of Chemistry, 2010)
An analytical method based on liquid chromatography with positive ion electrospray ionization (ESI) coupled to Tandem mass spectrometry detection (LC-MS/MS) was developed for the determination of nifedipine in human plasma using amlodipine as an internal standard. The analyte and internal standard were extracted from the plasma samples by solid phase extraction. The separation of nifedipine and amlodipine was achieved on a reversed phase (C18) column with a mobile phase consisting of 2 mM ammonium acetate (pH-3 by formic acid) (80:20 v/v). The linearity range was 4.01 to 297.03 ng/mL, inter-, intraday, accuracy and precision was found 91.65-99.93, 4.47-8.86, 96.07- 98.25 and 7.29-11.43, respectively.